Radio frequency interference in communications systems - Elbert, Bruce R. (Artech House, 2016)
This authoritative resource describes how to assess and mitigate RF interference in radio systems and presents effective methods to identify and resolve RFI before, during and after its appearance. Authored by a leading authority in the field, this book provides engineers and managers with the knowledge they need in the control of Radio Frequency Interference. Readers find practical guidance in an array of critical areas, including engineering of radiocommunication and wireless systems in light of RFI, identifying RFI modes, electromagnetic compatibility and spectrum sharing. Key concepts in evaluating radio frequency interference, propagation on obstructed paths, interference protection radio and RFI resolution and mitigation techniques such as filtering, spectral capture, radiolocation, cancellation and cognitive radio are covered in this book. This book concludes with prospective for RFI resolution in future radiocommunication systems. Publisher abstract.
Keywords: Radio -- Interference.; elektronické knihy; electronic books